PROPORSI TEPUNG MOCAF dan TAPIOKA DALAM PEMBUATAN KERUPUK MOROMI SEBAGAI MAKANAN CAMILAN - Setiawati, Bernadetta Budi (Jurnal Ilmu-Ilmu Pertanian, 2016)
The aims of this research is to determine differences in quality sensory moromi crackers with raw lour tapioca and mocaf composite in terms of colour, flavour, taste and texture; and the preference level panellists to crackers experimental results. Population in this research is moromi, mocaf flour and tapioca lour. This research method using laboratory experiments with the design of composite mocaf lour and tapioca lour are arranged with symbol and treatment A (1;1); B (3:2); C (2:3). Methods of data collection that is a subjective assessment by the sensory test, and test preferences. A data collection tool is not trained panellist for sensory test, and test preferences. Sensory test data analysis methods using single classification analysis of variance followed by Tukeys test, a test preference while using a descriptive analysis of the percentage. The results of Analysis of Variance (ANOVA) Single Classification, moromi crackers sensory quality of experimental results showed significant differences, composite mocaf and tapioca with comparison 1:1, 3:2, 2:3 the sensory quality of moromi crackers viewed from the aspect of colour, flavour, taste and texture. Best moromi crackers sample is a sample of crackers moromi witha basis of composite mocaf and tapioca with comparison 1:1 namely the aspect of colour 85%, flavour 79%, taste 78% and texture 76%.A test preferences panellist crackers moromi experimental results are sampled by comparison 1:1 (79,5%) shows the average value of the criteria very like and 3:2 (71,25%) shows the average value of the criteria like whereas the comparison samples 2:3 (69,75%)shows the average value sufficient criteria like.